Macrogynoplax duida, a New Species of Stonefly (Plecoptera: Perlidae) from Cerro Duida, Venezuela - Stark, Bill P. (Illiesia, 2011)
Macrogynoplax duida sp. n. is described from a male and female specimen collected from Cerro Duida, Venezuela, in 1928. The species is a close relative of M. geijskesii Zwick, known from Surinam.
Keywords: entomology; stonefly; Macrogynoplax; Plecoptera; new species; Cerro Duida; Venezuela; entomologija; vrbnice; nove vrste